Peran Pelayanan Pastoral dalam Memotovasi Jemaat untuk Mengikuti Ibadah Minggu di Gereja Kristen Protestan Indonesia Simangaronsang Resort Dolok Sanggul - Dini Andani Hartati Lumbantoruan; Herdiana Boru Hombing; Bestian Simangunsong; Rencan Carisma Marbun; Nurelni Limbong (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
This study aims to determine the role of pastoral care in motivating the congregation to attend Sunday services at GKPI Simangaronsang Resort Doloksanggul. Data were collected through semi-structured interviews and analyzed descriptively qualitatively. The lack of congregation motivation is caused by faith that has not grown, personal problems, economic problems, and conflicts between congregations and with church leaders. The results of the study indicate that the role of pastors and elders in motivating the congregation has not been maximized. Pastoral care such as visits and coaching of the congregation is very important to build motivation and strengthen faith and the relationship between the congregation and the church. Therefore, pastoral care is a vital aspect in church life and the motivation of congregational worship.